GREEN HALAL: SINERGI INDUSTRI HALAL DAN PEMBANGUNAN BERKELANJUTAN - Anisah, Dewi (An Natiq, 2024)
The Halal industry and sustainable development are two progressive issues closely related in the future. Industrial practices, particularly in the food industry, generate a significant amount of waste, and consumer awareness of environmental issues has sparked interest in "green halal" products that combine environmental principles and halal requirements. This research aims to define Green Halal, explore the synergy between the halal industry and sustainable development across various sectors, and identify the challenges and obstacles in implementing the concept of Green Halal. Using a literature review approach and analyzed descriptively, the results show that the synergy between the halal industry and the green economy supports human and environmental well-being. Challenges involve supplier awareness, supply chain collaboration, government regulations, and community support. It is noted that there is limited research on Green Halal in the pharmaceutical and fashion sectors, while the food and tourism sectors have received more attention. The synergy of Green Halal is expected to provide high-quality, environmentally friendly, and safe products for all living beings and promote a balance between humans and the natural ecosystem.